تأثير تدريبات للصلابة العقلية على مستوى أداء مهارة الضرب الساحق من المنطقة الأمامية لناشئ الكرة الطائرة - الدسوقي، خالد محمد زيادة; جادو، المرزوقي محمد المرزوقي; قنديل، شريف محروس محمد; منصور، نشأت محمد أحمد (جامعة المنصورة - كلية التربية الرياضية, 2016)
This research aims to recognize the effect of using mental toughness drills program on the level of performance smash skill from the front zone for junior volleyball under 17 years. The researcher used the experimental method and applied the research on a sample consist of 16 juniors, selected by the purposive manner from the volleyball juniors under 17 years from El Mansoura Stadium Youth Center. Then divided it into two equal groups the first is an experimental group and the second is a control group consist of 8 juniors. This supposed training program showed a positive effect on the skill variables and mental toughness variables under investigation the researcher recommended to the necessity of the presence of psychological prepared inside volleyball devices and utilize from the mental toughness supposed program under investigation in juniors training in development psychological skills in junior to upgrade the level of skill for junior volleyball.
يهدف البحث للتعرف على تأثير تدريبات للصلابة العقلية على مستوى أداء مهارة الضرب الساحق من المنطقة الأمامية لناشئ الكرة الطائرة، واستخدم الباحث المنهج التجريبي وتم اختيار عينة قوامها 16 ناشئ بالطريقة العمدية من ناشئ كرة الطائرة تحت 17 سنة بمركز شباب ستاد المنصورة، وتم تقسيمهم إلى مجموعتين متكافئتين أحداهما تجريبية، والأخرى ضابطة قوام كل منها ٨ ناشئين. وأظهر البرنامج التدريبي المقترح تأثيرا إيجابيا على المتغيرات المهارية، ومتغيرات الصلابة العقلية قيد البحث، وأوصى الباحث بضرورة تواجد المعد النفسي داخل أجهزة الكرة الطائرة، وضرورة الإستفادة من برنامج تدريبات الصلابة العقلية قيد البحث في تنيمة المهارات النفسية للناشئين للارتقاء بالمستوى المهارى لناشئ الكرة الطائرة.
Keywords: التدريب الرياضي -- الكرة الطائرة